2012
DOI: 10.1002/rcm.6449
|View full text |Cite
|
Sign up to set email alerts
|

Matrix effect in matrix‐assisted laser desorption/ionization mass spectra of derivatized oligomeric polyols

Abstract: The obtained results show that matrix molecules can participate as reactive species in MALDI-ToF-MS experiments. The matrix should be carefully chosen when a derivatization approach is applied because the analysis of spectra of the completely derivatized products is particularly desirable in the quantitative determination of functional end-groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In the positive ion mode, almost the sole signal is due to {[Cat + ] 2 [An − ]} + clusters, while the negative ion spectra contain not only their {[Cat + ][An − ] 2 } − counterparts, but also the anionic complexes with metal cations. Formation of such complexes is not unusual in MALDI even in the absence of the respective metals in the sample, among their hypothetic sources being the material of the target plate. The most abundant of the complex anions observed was {2[An − ]+Na + } − and the rest included {2[An − ]+K + } − , {2[An − ]+Cu + } − , and sometimes {3[An − ]+Ca 2+ } − .…”
Section: Resultssupporting
confidence: 90%
“…In the positive ion mode, almost the sole signal is due to {[Cat + ] 2 [An − ]} + clusters, while the negative ion spectra contain not only their {[Cat + ][An − ] 2 } − counterparts, but also the anionic complexes with metal cations. Formation of such complexes is not unusual in MALDI even in the absence of the respective metals in the sample, among their hypothetic sources being the material of the target plate. The most abundant of the complex anions observed was {2[An − ]+Na + } − and the rest included {2[An − ]+K + } − , {2[An − ]+Cu + } − , and sometimes {3[An − ]+Ca 2+ } − .…”
Section: Resultssupporting
confidence: 90%
“…Although this type of ionization is considered softer than electron ionization, the observed ions are typically still fragments of their parent molecules (De Hoffmann and Stroobant, 1999). Furthermore, the measured intensity of one compound does not only depend on its concentration but also on the concentration of all other compounds present (the so-called matrix effect), making quantification challenging (Ellis et al, 2014;Borisov et al, 2013). We recorded the mass spectra of 819 filter samples in an m/z range 65-500 thomsons (Th; 1 Th = 1 Da e −1 , where e is the elementary charge, ion gate at m/z 60 Th) using a laser-desorption/ionization time-of-flight (ToF) MS (Shimadzu Axima Confidence, Shimadzu-Biotech Corp., Kyoto, Japan) equipped with an N 2 laser (wavelength 337 nm, frequency 50 Hz, laser pulse width 3 ns, 130-180 µJ pulse −1 ) in the positive reflectron mode.…”
Section: Instrument and Measurement Settingsmentioning
confidence: 99%
“…Such a situation has been observed in the analysis of silylated polyols when carboxyl-containing matrices (DHB, HABA) could subtract silyl groups from derivatized analytes during co-crystallization. 47 It has also been shown that, for the analysis of monomeric and pre-polymeric isocyanates by MALDI mass spectrometry, their 1-(2-methoxyphenyl) piperazine derivatives were suitable. 48 Among the most interesting derivatization agents are those allowing the introduction of a group already containing covalently-bonded charge or promoting the formation of a charge.…”
Section: Introductionmentioning
confidence: 99%